A Fixed-Point Iteration Scheme for Model Predictive Torque Control of PMSMs. Issue 20 (2018) - Englert, Tobias; Graichen, Knut
Abstract: This paper proposes a tailored fixed-point iteration scheme for the model predictive torque control of permanent magnet synchronous machines. Both spherical voltage and current constraints are taken into account using a projection function and an augmented Lagrangian approach. The fixed-point scheme is a continuous control set approach and is based on the nonlinear dq-model. The inductivities and permanent magnet flux are modelled current-dependently and therefore account for saturation and parasitic effects. Experimental results on a standard dSpace hardware show the performance as well as the very small computational load of the proposed torque control scheme, which is therefore suitable for an embedded implementation.